Energy‐restricted interventions are effective for the remission of newly diagnosed type 2 diabetes: A systematic review of the evidence base - Elizabeth Jacob; Amanda Avery (Wiley, 2021)
Abstract Background Type 2 diabetes (T2D) is a chronic, progressive disease. Caloric restriction and subsequent weight loss have been associated with both improvements and, in some cases, remission of T2D. Aim To systematically review the safety and effectiveness of calorie‐restricted diets on weight change and the remission of T2D. Methods Electronic databases were searched. Intervention trials including a calorie restriction, published between 2010 and 2020, evaluating the remission of T2D (HbA1c <6.5% without diabetes medication) were selected. Risk of bias was assessed. Results Eight trials met inclusion criteria including four randomized controlled and four single‐arm trials. Three controlled trials found greater remission in the calorie‐restricted arm (p < 0.05). A recent diagnosis of diabetes was associated with higher remission rates (75%-80%) with an inverse association between duration of diabetes and rate of remission (r = −0.94). A higher level of remission was observed with greater calorie restriction in non‐new diagnosis studies. Greater weight loss was associated with increasing rates of remission (r = 0.83). No reported adverse events led to withdrawal from trials. There was great heterogeneity in study design. Conclusion Remission rate of T2D achieved through calorie restriction is high and similar to that reported in the bariatric surgery literature. Remission should be the aim at diagnosis and calorie restriction could be used to achieve this. The target weight loss should be >10% body weight in people with obesity. More research is needed into the optimum level of calorie restriction and the support required for long‐term remission. National guidelines should be updated to reflect recent evidence.